ChemInform Abstract: Ruthenium Complexes of Tetradentate Bipyridine Ligands: Highly Efficient Catalysts for the Hydrogenation of Carboxylic Esters and Lactones. Issue 7 (29th January 2015) - Li, Wei; Xie, Jian‐Hua; Yuan, Ming‐Lei; Zhou, Qi‐Lin
Abstract A new type of readily available, air‐stable Ru‐complex is described.